How Small Retail Stores React on Covid-19 Pandemic Constraints - Vaz, Blanche Vailankani; Mendonca, Farah Felizinha (Universitas Prasetiya Mulya, 2022)
This research investigates ‘The Impact of Covid-19 Pandemic on Small Retail Stores in India’. Its primary focus was to find out the various obstacles faced, strategies implemented and measures adopted by small retail stores during the Covid-19 pandemic and if there were any variations among the various retail stores in South Goa. Data was obtained from 69 small retail stores of South Goa namely medical, general, clothing and electronic stores. A One-way ANOVA test was used to analyze the data responses. Results indicated there were no much variations among the retail stores with respect to the obstacles faced, strategies implemented and measures adopted during Covid-19 pandemic. Due to the pandemic a large number of small retail stores faced many constraints. This paper elucidates how small retail stores can strategize and implement various ways to meet the needs of the customers in case of any such future emergencies.